2020
DOI: 10.1108/nfs-04-2020-0129
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of antioxidant activity, minerals and chemical constituents of edible mahua (Madhuca longifolia) flower and fruit of using principal component analysis

Abstract: Purpose Flowers and fruits of Madhuca longifolia (Koenig) (mahua) tree are edible and used as traditional Indian medicines. The physicochemical properties of different parts of mahua are investigated. This study aims to estimate the different mineral contents, polyphenols compounds and antioxidant activities by 2,2-diphenyl-1-picrylhydrazyl inhibition, reducing power, free radical scavenging activity using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…In the case of aronia fruits, which are not a rich source of vitamin C, the grouping is based on the content levels of chlorogenic acids and total polyphenols, and high results in the DPPH test. In methua fruit (Madhuca longifolia), which is primarily a source of flavonoids when ripe, clustering by the new variable PC into ripe and unripe fruit was also observed [39]. Similarly, Gomez et al [40] and Rajkumar et al [41] described the study of the Chinese variety of Satsuma mandarin (C. reticulata) and banana fruits, respectively, based on their degrees of ripeness, using PCA analysis.…”
Section: Pca Analysismentioning
confidence: 88%
“…In the case of aronia fruits, which are not a rich source of vitamin C, the grouping is based on the content levels of chlorogenic acids and total polyphenols, and high results in the DPPH test. In methua fruit (Madhuca longifolia), which is primarily a source of flavonoids when ripe, clustering by the new variable PC into ripe and unripe fruit was also observed [39]. Similarly, Gomez et al [40] and Rajkumar et al [41] described the study of the Chinese variety of Satsuma mandarin (C. reticulata) and banana fruits, respectively, based on their degrees of ripeness, using PCA analysis.…”
Section: Pca Analysismentioning
confidence: 88%
“…Tannins [100] Faizi et al (2017) [101] Dar et al [102] Gautam et al (2015) [103] 23 [104] Singh et al (2020) [105] Mansuri and Yadav (2020) [106] 24 [107] Ghosh et al (2014) [108] 25 Hinglaaj…”
Section: Phytochemical Properties and Medicinal Properties Of The Med...mentioning
confidence: 99%
“…The obtained values were 58.13 µg/ml for the bark extract and 47.56 µg/ml for ascorbic acid (8). The antioxidant activity of the aqueous acetone extract of flowers and fruits of the plant was also determined by the DPPH scavenging activity and it was evaluated that the DPPH activity of the flower (89.4±0.1) was higher than that of the fruits both ripe (88.2±1) and unripe (88.6±0.1) and it was reported that the antioxidant activity arises due to the amount of TPC (total phenolic content) and TFC (total flavonoid content) (9).…”
Section: Pharmacological Properties Anti-oxidant Activitymentioning
confidence: 99%